2023
DOI: 10.3847/1538-4357/acdcf8
|View full text |Cite
|
Sign up to set email alerts
|

Tianwen-1 and MAVEN Observations of the Response of Mars to an Interplanetary Coronal Mass Ejection

Abstract: Interplanetary coronal mass ejections (ICMEs) are solar transients that have significant effects on the upper atmosphere and ionosphere of Mars. The simultaneous spacecraft observations from Tianwen-1/MOMAG in solar wind and multiple instruments on board the Mars Atmosphere and Volatile Evolution (MAVEN) in the Martian upper atmosphere are used to study the response of Mars to an ICME. The ICME was observed at Mars by Tianwen-1 and MAVEN at 00:00 UT on 2021 December 10, which was earlier observed by BepiColomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The deformation of the IMF structure outside of the Parker spiral causes the deviation of the prediction. Moreover, the prediction results that the arrival time of CIR-1 is earlier than expected at BepiColombo but later than expected at Mars also indicate that the rotation of the CIRs is not constant (Allen et al 2020) Previous studies have identified CME events that occurred during the study period (e.g., Chi et al 2023aChi et al , 2023bYu et al 2023). These CMEs may have cleared some of the ambient solar wind plasma (Chi et al 2020), leading to a rarefied and disturbed solar wind; consequently, the prediction for the in situ parameters of CIRs is affected.…”
Section: Discussionmentioning
confidence: 90%
“…The deformation of the IMF structure outside of the Parker spiral causes the deviation of the prediction. Moreover, the prediction results that the arrival time of CIR-1 is earlier than expected at BepiColombo but later than expected at Mars also indicate that the rotation of the CIRs is not constant (Allen et al 2020) Previous studies have identified CME events that occurred during the study period (e.g., Chi et al 2023aChi et al , 2023bYu et al 2023). These CMEs may have cleared some of the ambient solar wind plasma (Chi et al 2020), leading to a rarefied and disturbed solar wind; consequently, the prediction for the in situ parameters of CIRs is affected.…”
Section: Discussionmentioning
confidence: 90%